Financial and corporate governance of XBRL adopters in Indonesia - Kersna Minan; Mochammad Fahlevi (Kusuma Negara Business School, 2021)
Extensible Business Reporting Language (XBRL) is an XML language-based business reporting software standard that is used to manage a company's financial data based on international financial standards. XBRL is used to ensure the accessibility of business information and transparency by using a uniform format and is usually used by business intelligence departments. The financial statements of a company are the main source of company information. Because with financial reports, all stakeholders of a company can have an overview of the business journey of a company. XBRL will increase transparency and will further improve corporate governance. Disclosure with XBRL will be able to show the profile of the company's corporate governance (Tohang et al., 2020). XBRL will also play a role in the decision-making process. XBRL will increase transparency and will further improve corporate governance. The adoption of XBRL in corporate financial reporting will increase transparency and quality of information. This standardized XBRL format makes it easy to use information across different platforms and applications so that information will be more transparent. The quality of information increases because of the ability to search by users who are getting faster and more precise.